Work Motivation, Training, Commitment, and Discipline on Employee Satisfaction and Performance in PT. Sumber Mas Baru Pekanbaru - Merinayati Panjaitan; Asmara Hendra Komara; Harry Patuan Panjaitan (International Conference on Business Management and Accounting, 2023)
This study aims to test the magnitude of the influence of motivation, training, commitment, and discipline to the satisfaction and performance of employees at PT. Sumber Mas Baru in Pekanbaru. Questionnaire as a data collector of 70 respondents proportionally all employees who work at PT. Sumber Mas Baru, tested using SPSS 21.0 Data Analysis and Path Analysis PLS (Path Smart PLS). Test results show that discipline has no direct and insignificant effect on satisfaction, commitment has no direct and insignificant effect on satisfaction, discipline has no direct or indirect influence and no significant to performance, commitment has no direct and indirect effect and not significant on the performance, the training does not directly or indirectly influence and not significant to the performance, the training has a direct and significant positive impact on satisfaction, and satisfaction has a direct and significant positive effect on the performance of the employees of PT. Sumber Mas Baru. In this test there are variables that are removed the variable of motivation karna experience multikorelasi both to satisfaction and performance.